Sex Differences in the Association of Urinary Concentrations of Phthalates Metabolites with Self-Reported Diabetes and Cardiovascular Diseases in Shanghai Adults - Dong, Ruihua (Int J Environ Res Public Health, 2017)
Phthalate exposure was reported to be associated with diabetes mellitus (DM) and cardiovascular disease (CVD). Yet, reported associations and the potential sex differences are inconsistent. We conducted a cross-sectional study involving 2330 participants in the Fall of 2012. Urinary metabolites of 10 phthalates were measured. The status of having DM and CVD-related outcomes were self-reported. In the overall study population, the logistic regression analyses showed that the urinary levels of mono-2-ethyl-5-oxohexyphthalate (MEOHP), mono-2-ethyl-5-hydroxyhexylphthalate(MEHHP) and mono-2-ethyl-5-carboxypentylphthalate (MECPP) were positively associated with DM. Higher urinary levels of monomethyl phthalate (MMP) and mono-2-carboxymethyl-hexyl phthalate (MCMHP) were associated with increased odds of hyperlipidemia, while mono-2-ethylhexylphthalate (MEHP) was significantly inverse-associated with hyperlipidemia. We did not observe significant associations for other CVD-related outcomes with phthalate metabolites. When stratifying by sex, MEHHP, MEOHP, MECPP, MCMHP and the micromolar sums of the oxidative metabolites of DEHP (ΣDEHP(ox)) were all significantly related to DM in males, but not in females. No significant sex differences were found in CVD-related outcomes, except the sporadic associations between phthalates and hyperlipidemia. These findings highlight the importance of investigating the sex-specific relationship between phthalates exposure and DM.